问题 解答题
简便计算
(1)4.85-
5
9
+5.15-
4
9

(2)
1
9
×(4
3
4
÷
5
18
-3.6+6.15×3
3
5
)

(3)
3
4
÷[(
4
5
+
1
4
3
7
]

(4)1
1
6
+3
1
12
+5
1
20
+7
1
30
+9
1
42
答案

(1)4.85-

5
9
+5.15-
4
9

=4.85+5.15-(

5
9
+
4
9
),

=10-1,

=9;

(2)

1
9
×(4
3
4
÷
5
18
-3.6+6.15×3
3
5
),

=

1
9
×(4.75×
18
5
-3.6+6.15×3.6),

=

1
9
×[(4.75+6.15-1)×3.6],

=

1
9
×9.9×3.6,

=3.96;

(3)

3
4
÷[(
4
5
+
1
4
3
7
],

=

3
4
÷[
21
20
×
3
7
],

=

3
4
÷
9
20

=

3
4
×
20
9

=1

2
3

(4)1

1
6
+3
1
12
+5
1
20
+7
1
30
+9
1
42

=(1+3+5+7+9)+(

1
6
+
1
12
)+(
1
20
+
1
30
+
1
42

=25+(

2
12
+
1
12
)+(
3
60
+
2
60
+
1
42

=25+

3
12
+
5
60
+
1
42

=25+(

3
12
+
1
12
+
1
42

=25+

1
3
+
1
42

=25+(

14
42
+
1
42
),

=25

15
42

=25

5
14

填空题
问答题 案例分析题